AFB smear positive 1+: a dominant factor in Pulmonary TB household transmission - Alinea Dwi Elisanti; Diany Yoke Safira; Efri Tri Ardianto (Health Science Journal of Indonesia, 2020)
Latar belakang: TBC menjadi masalah kesehatan dunia, termasuk Indonesia karena kasus baru TB paru terus meningkat. Penelitian ini mengkaji faktor dominant yang mempengaruhi penularan kontak serumah pasien TB paru. Metode: Studi observasional dengan desain analitik cross sectional ini menggunakan populasi seluruh penderita dan anggota keluarga pasien TB paru di Puskesmas Kedundung tahun 2015 2016. Sampel sejumlah 52 orang dihitung menggunakan rumus besar sampel infinith dan diambil secara konsekutif. Variabel penelitian meliputi perilaku pencegahan, Gradasi BTA dan penularan kontak serumah. Pengumpulan data menggunakan lembar wawancara, lembar pengumpul data, sputum pot steril. Data dianalisis menggunakan uji Spearman Rank dan uji regresi logistik binary dengan tingkat signifikansi 0,05. Hasil: Perilaku pencegahan (p=0.093), BTA positive 2+ (p=0.377) tidak berpengaruh terhadap penularan kontak serumah pasien TB paru, sedangkan BTA positive 1+ mempengaruhi penularan kontak serumah pasien TB paru (p= 0,007). Nilai Exp (B) BTA positif (1+) menunjukkan 12,144 artinya pasien BTA positif (1+) memiliki risiko 12,144 kali lebih tinggi menularkan ke kontak serumah dibandingkan dengan BTA positif (3+). Sedangkan pasien BTA positif (2+) memiliki risiko 3,328 kali menularkan ke kontak serumah dibandingkan dengan BTA positif (3+). Kesimpulan: Pasien TB paru dengan pemeriksaan BTA positif (1+) menjadi faktor dominan yang mempengaruhi penularan kontak serumah pasien TB paru. Upaya komunikasi dan edukasi personal higiene, tingkat kepatuhan pengobatan pasien TB paru perlu ditingkatkan untuk menekan kejadian baru TB paru. Kata kunci: Gradasi BTA, TB Paru, Perilaku Pencegahan, Penularan Kontak Rumah Tangga Abstract Background: Tuberculosis has become a global health problem, included in Indonesia, new cases of pulmonary TB increase continuously. This study examined the dominant factors that influenced the transmission of household contacts in pulmonary TB patients. Methods: This observational study was a cross-sectional analytic design which used a population of all patients and family members of pulmonary TB patients at the Kedundung Health Center in 2015 until 2016. A sample of 52 people was counted using the infinith sample size formula and taken consecutively. Research variables include prevention behavior, AFB smear gradation, and household contact transmission. Collecting data used interview sheets, data collection sheets, sterile sputum pots. Data was analyzed by chi-square test and binary logistic regression test with a significance level of 0.05. Results: Prevention behavior (p=0.093), AFB smear-positive 2+ (p=0.377) did not affect on household contact transmission in pulmonary TB patients, whereas AFB smear-positive 1+ affected household contacts transmission of pulmonary TB patients (p=0.007). The value of Exp (B), AFB smear-positive (1+) have a risk of 12.144 times transmitting to household contact when compared to AFB smear-positive (3+). Whereas patients with AFB smear-positive (2+) have a risk of 3,328 times transmitting to household contact when compared with AFB smear-positive 3+. Conclusion: Pulmonary TB patients with AFB smear-positive (1+) was the dominant factor affecting household contact transmission. Communication and personal hygiene education efforts, the level of adherence in the treatment of pulmonary TB patients needs to be increased to suppress the new incidence of pulmonary TB. Keywords: AcidFast Bacilli (AFB) gradation, pulmonary TB, Prevention Behavior, Transmission of Household Contacts